Substituting Tyr138 in the active site loop of human phenylalanine hydroxylase affects catalysis and substrate activation. Issue 7 (12th June 2017) - Leandro, João; Stokka, Anne J.; Teigen, Knut; Andersen, Ole A.; Flatmark, Torgeir
Abstract : Mammalian phenylalanine hydroxylase (PAH) is a key enzyme inl ‐phenylalanine (l ‐Phe) metabolism and is active as a homotetramer. Biochemical and biophysical work has demonstrated that it cycles between two states with a variably low and a high activity, and that the substratel ‐Phe is the key player in this transition. X‐ray structures of the catalytic domain have shown mobility of a partially intrinsically disordered Tyr 138 ‐loop to the active site in the presence ofl ‐Phe. The mechanism by which the loop dynamics are coupled to substrate binding at the active site in tetrameric PAH is not fully understood. We have here conducted functional studies of four Tyr 138 point mutants. A high linear correlation ( r 2 = 0.99) was observed between their effects on the catalytic efficiency of the catalytic domain dimers and the corresponding effect on the catalytic efficiency of substrate‐activated full‐length tetramers. In the tetramers, a correlation ( r 2 = 0.96) was also observed between the increase in catalytic efficiency (activation) and the global conformational change (surface plasmon resonance signal response) at the samel ‐Phe concentration. The new data support a similar functional importance of the Tyr 138 ‐loop in the catalytic domain and the full‐length enzyme homotetramer. Abstract : The conformation and function of mammalian phenylalanine hydroxylase is triggered by binding of its substrate, and regional motion of the Tyr 138 ‐loop is a key element in this process. Mutagenesis of Tyr 138 reported here, together with previous crystallographic‐structural modeling, infers that the functional information obtained about the Tyr 138 ‐loop in the catalytic domain homodimer, can be extended to include the full‐length enzyme homotetramer.